Factors Related to Health Promoting Behaviors of Village Health Volunteers in Muang District, Chon Buri Province - Kanchanaudom, Patcharapa; Rukkwamsuk, Suntharee; Wankrathok, Suppakorn (Journal of Nursing, Siam University, 2020)
The village health volunteers who have an influence on public health care should have an appropriate health promotion behavior as a good role model of health for people. This descriptive research was aimed to study the relationship between health promoting behaviors and predisposing, enabling, and reinforcing factors of village health volunteers. The sample consisted of 370 village health volunteers in Muang district, Chon Buri province was selected using stratified random sampling technique. Data was collected using four rating scale questionnaire and the reliability of the questionnaires were tested by Cronbach’s alpha coefficient method. The confidence coefficient of each questionnaire was range between 0.82-0.86. Analysis of the collected data was carried out by descriptive statistical analysis, and Pearson’s Correlation Coefficient analysis. The results showed that: Overall health promoting behaviors of village health volunteers were at a good level. ( =2.81, S.D.= 0.39). Predisposing factors of the perception of self-efficacy and health status were related to health promoting behaviors (p<.01). Enabling factors to the work duration of village health volunteers were not related to health promoting behaviors. Reinforcing factor of perceived motivation to perform the duties (p<.01), and social support from the public health officials was related to health promoting behaviors (p<.001). The outcome of this study could be used as a guideline for promoting self-efficacy, perception of health status, perception of motivation to perform the duties and providing social support from public health officials to village health volunteers. This could build the confidence in the village health volunteers for their own health care and improve appropriate health promotion behavior.